2000
DOI: 10.1002/1097-0215(20001215)88:6<992::aid-ijc24>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trichostatin A on cell growth and expression of cell cycle- and apoptosis-related molecules in human gastric and oral carcinoma cell lines

Abstract: The effect of trichostatin A (TSA), histone deacetylase inhibitor, on cell growth and the mechanism of growth modulation was examined in 8 gastric and 3 oral carcinoma cell lines which included 9-cis-retinoic acid resistant (MKN-7 and Ho-1-N-1) and IFN-␤ resistant cell lines (MKN-7, -28 and -45). TSA inhibited growth in all cell lines examined. Apoptotic cell death was confirmed by apoptotic ladder formation and induction of a cleaved form (85 kDa) of poly (ADP-ribose) polymerase (PARP) induction. TSA enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 17 publications
5
70
0
7
Order By: Relevance
“…Inhibition of HDAC activity is known to revert the phenotype of transformed cells (13,14) into nontransformed phenotypes (2,13,14). Since the most clearly changed characteristic is an alteration of cytoskeletal organization, we investigated whether TSA regulates the functions of proteins involved in cytoskeletal organization.…”
Section: Detransformation Of Ras-transformed Fibroblasts By Tsa-mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of HDAC activity is known to revert the phenotype of transformed cells (13,14) into nontransformed phenotypes (2,13,14). Since the most clearly changed characteristic is an alteration of cytoskeletal organization, we investigated whether TSA regulates the functions of proteins involved in cytoskeletal organization.…”
Section: Detransformation Of Ras-transformed Fibroblasts By Tsa-mentioning
confidence: 99%
“…Recently, it has been shown that inhibition of HDAC activity by TSA is able to revert the morphological changes seen following the transformation of cells in culture with v-sis and v-ras oncogenes (12). TSA-treated cells become more flattened and have well organized actin stress fibers (13,14). Therefore, TSA has an ability to detransform at least ras-transformed fibroblasts.…”
mentioning
confidence: 99%
“…In addition, the natural product HDACIs of the trapoxin class and trichostatin were shown to activate the p21 promoter, increase p21 protein levels, inhibit cyclin-dependent kinase 2 kinase activity, reduce retinoblastoma (Rb) phosphorylation, and cause cell cycle arrest or apoptosis in three human tumor cell lines (21,28,29). NVP-LAQ824, our novel synthetic HDACI, showed similar properties at submicromolar concentrations.…”
Section: Introductionmentioning
confidence: 96%
“…Cell proliferation was measured using an adaptation of published procedures (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxy-phenyl)-2-(4-sulfonyl)-2H-tetrazolium assay) as described previously (29). The CellTiter 96 AQueous Non-Radioactive Cell Proliferation Assay was performed according to the manufacturer's protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Histone hyperacetylation is thought to relax the chromatin structure and allow transcription factors to access promoters (Luger et al, 1997;Luger and Richmond, 1998). We have reported that trichostatin A (TSA), a histone deacetylase (HDAC) inhibitor, induces expression of p21 Waf1 and HLTF in GC cell lines (Suzuki et al, 2000;Hamai et al, 2003). HDACs are separated into three distinct classes on the basis of their homologies to yeast transcriptional repressors (North et al, 2003).…”
Section: Introductionmentioning
confidence: 99%